A capacitive-inductive dual modality imaging system for non-destructive evaluation applications. (1st January 2020) - Yin, Xiaokang; Fu, Jiaming; Li, Wei; Chen, Guoming; Hutchins, David A.
Highlights: A new capacitive-inductive dual modality imaging system for NDE is proposed. The proposed system is useful to inspect insulator-conductor hybrid structures. A capacitive image and an inductive image can be obtained after one scan. Visual indications in the two images can berelated to defect types and locations. Abstract: For many non-destructive evaluation (NDE) applications, more information can be obtained by using different techniques, especially when the techniques are sensitive to different types of defects. However separate inspections are not always practical due to time and cost constraints. Therefore, an inspection system combing more than one modalities would have many advantages. A dual modality imaging system is thus proposed which can automatically switch between capacitive imaging and inductive imaging modes. Instead of using a physical combination of two sensors, the proposed system employs a coplanar coil pair as a sensor, and the modality switching is done by changing the wiring schemes through program-controlled switch box. After a single scan over the specimen under test, two types of images, namely capacitive and inductive, can be obtained by the proposed system. For an insulated metallic structure, the capacitive image contains the defect information in the insulation layer and on the top surface of the conducting layer, while the inductive image contains the defect information within the conducting region. The proposed integration of the two imaging modalities in a single system does not introduce any interference between the modes and provides more information on the defects with a reduced testing time and production cost on hardware and software compared to using two NDE techniques separately. A theoretical explanation of the imaging mechanisms for the capacitive and inductive modes are provided. The results of finite element modelling show perturbation of the probing fields due to defects in the two imaging modes. Experimental results from a dual modality imaging system are also presented, demonstrating detection of defects in insulator-metal hybrid structures to verify the effectiveness of this approach.